Reconfiguring Social Capital through Ahmad Dahlan’s Welas Asih Ethics - Akbar Yusuf (Yayasan Rumah Peneleh, 2021)
The purpose of this article is to deconstruct the Political Economic of Accounting (PEA) and construct Social Capital through the KH. Ahmad Dahlan's Welas Asih (or compassionate) ethics. The analysis technique employed was a deconstruction approach to interpret the PEA theory or framework. Further, Social Capital was constructed using KH. Ahmad Dahlan's Ethics of Welas Asih. PEA places social relations represented by various social institutions that regulate strategies for the realization of rights and obligations, while the economic order does not have transcendental relationships as motivation in organizing the power of economic resources to generate social capital. PEA also does not guarantee or present values that have characteristics specifics in each company or country. Welas Asihethics emphasizes social capital as the output of organizing economic power, which has divine transcendental values, namely the fear of denying religion and the fear of being a wretched person in the main worship of Almighty God